The Theory and Practice of Geographical and Logistical Provision of Sustainable Development of Urbotourism in the Conditions of Overturism (On Example of the "Concept of Tourism Decentralization" in City of Lviv) - Смирнов, Ігор Георгійович (Київський національний університет імені Тараса Шевченка, 2019)
The aim of the study. Theoretical substantiation and practical application of geographical and logistical support of urban tourism in the conditions of overtourism on the example of Lviv and the corresponding "Concept of tourism decentralization ". Research methodology. It is based on geographical and logistical categories in relation to urban tourism in the conditions of overtourism, in particular these are indicators of capacity of tourist destination, its resource potential and potential of hotel-restaurant and transport infrastructure, as well as reflection of regional (geographical) features of tourism processes, in particular tourist decentralization, concentration and dispersion. Results of the research. The theoretical concept presented in the article has been practically tested in the practice of tourism in Lviv, in particular on the example of "Concepts of tourism decentralization ". Proposals for optimization and improvement of geospatial organization of tourism in Lviv included: a) vertical and horizontal diversification of tourist flows in the city center, solving the problem of tourist waste, limiting the cases of intim tourism in favor of conference and blogger tourism, finally strengthening the requirements of tourists safety in particular in the areas of their accommodation, food and entertainment. Some of these proposals have already been taken into account in the tourism management of Lviv, so, in 2019, the post of Deputy Mayor for Security was introduced. Scientific novelty. For the first time in Ukraine the phenomenon of overtourism and its impact on urban tourism with the use of logistic and geographical approaches is considered. For the first time the problems of overtourism in the conditions of cities have been identified and the ways of solving this problem on example of Lviv are considered. Practical importance. Theoretical provisions have been applied to solve practical problems of development of tourism industry of big city in conditions of sharp increase of tourists number, as, for example, in Lviv, and a number of practical measures have been proposed to reduce the negative effects of overtourism, in particular the excessive concentration of tourists in the central part of the city, increasing volume of waste, occurrence of intimate tourism, exacerbation of tourist safety problems, etc. Accordingly, it is proposed to expand the tourist territory of the city due to the vertical and horizontal diversification of tourist flows, a diversified approach to determining business tax depending on its location in the city center or on the periphery ("garbage tax"), the development of conference and blogger tourism, increased attention and control of tourist security problems especially in spheres of food, accommodation, transportation, entertainment and more.

Мета дослідження. Теоретичне обґрунтування та практичне застосування географічного та логістичного забезпечення урботуризму в умовах овертуризму на прикладі м. Львова та відповідної «Концепції децентралізації туризму». Методика дослідження. Базується на географічних та логістичних категоріях по відношеню до урботуризму в умовах овертуризму, зокрема це показники пропускної спроможності туристичної дестинації, її ресурсного потенціалу та потенціалу готельно-туристичної та транспортної інфраструктури, а також відображення регіональних (географічних) особливостей туристичних процесів, що розглядаються, зокрема туристичної децентралізації, концентрації та дисперсії. Результати дослідження. Теоретична концепція, викладена у статті, була практично апробована на туристичній практиці м. Львова, зокрема на прикладі «Концепції децентралізації туризму». Пропозиції з оптимізації та вдосконалення геопросторової організації туризму у м. Львові включили: а) вертикальну та горизонтальну диверсифікацію туристичних потоків у середмісті, вирішення проблеми туристичних відходів, обмеження випадків інтим-туризму на користь конференц та блогер-туризму, нарешті посилення вимог безпеки туристів, зокрема у сферах їхнього розміщення, проживання та розваг. Деякі з цих пропозицій вже враховані в управлінні туризмом м. Львова, так, у 2019 р. запроваджено посаду заступника мера з питань безпеки. Наукова новизна. Вперше в Україні розглянуто явище овертуризму та його вплив на урботуризм із застосуваннм логістичного та географічного підходів. Вперше виділено проблеми овертуризму в умовах міст та розглянуто шляхи вирішення цієї проблеми на прикладі м. Львова. Практична значимість. Теоретичні положення було прикладено до вирішення практичних проблем розвитку туристичної галузі великого міста в умовах різкого зростання числа туристів, як, наприклад, у м. Львові, і запроновано низку практичних заходів для зменшення негативних наслідків овертуризму, зокрема надмірної концентрації туристів у центральній частині міста, збільшенні обсягів відходів, появи випадків інтим-туризму, загострення проблем безпеки туристів тощо. Відповідно пропонується розширити туристичну територію міста за рахунок вертикальної та горизонтальної диверсифікації туристичних потоків, диверсифікований підхід до визначення податку для бізнесу залежно від його розміщення у центрі міста або на периферії («сміттєвого податку»), розвиток конференц та блогер-туризму, посилена увага та контроль проблем безпеки туристичного харчування, проживання, транспортування, розваг тощо.
Теорія та практика географічного та логістичного забезпечення сталого розвитку урботуризму в умовах овертуризму (на прикладі «Концепції децентралізації туризму» м. Львова)
Keywords: овертуризм; урботуризм; туристична концентрація; туристична дисперсія; логістичний аспект; географічний аспект; overtourism; urban tourism; tourist concentration; tourist dispersion; logistic aspect; geographical aspect